What happens after inbreeding avoidance? Inbreeding by rejected relatives and the inclusive fitness benefit of inbreeding avoidance. - A Bradley Duthie (PLoS ONE, 2015)
Avoiding inbreeding, and therefore avoiding inbreeding depression in offspring fitness, is widely assumed to be adaptive in systems with biparental reproduction. However, inbreeding can also confer an inclusive fitness benefit stemming from increased relatedness between parents and inbred offspring. Whether or not inbreeding or avoiding inbreeding is adaptive therefore depends on a balance between inbreeding depression and increased parent-offspring relatedness. Existing models of biparental inbreeding predict threshold values of inbreeding depression above which males and females should avoid inbreeding, and predict sexual conflict over inbreeding because these thresholds diverge. However, these models implicitly assume that if a focal individual avoids inbreeding, then both it and its rejected relative will subsequently outbreed. We show that relaxing this assumption of reciprocal outbreeding, and the assumption that focal individuals are themselves outbred, can substantially alter the predicted thresholds for inbreeding avoidance for focal males. Specifically, the magnitude of inbreeding depression below which inbreeding increases a focal male's inclusive fitness increases with increasing depression in the offspring of a focal female and her alternative mate, and it decreases with increasing relatedness between a focal male and a focal female's alternative mate, thereby altering the predicted zone of sexual conflict. Furthermore, a focal male's inclusive fitness gain from avoiding inbreeding is reduced by indirect opportunity costs if his rejected relative breeds with another relative of his. By demonstrating that variation in relatedness and inbreeding can affect intra- and inter-sexual conflict over inbreeding, our models lead to novel predictions for family dynamics. Specifically, parent-offspring conflict over inbreeding might depend on the alternative mates of rejected relatives, and male-male competition over inbreeding might lead to mixed inbreeding strategies. Making testable quantitative predictions regarding inbreeding strategies occurring in nature will therefore require new models that explicitly capture variation in relatedness and inbreeding among interacting population members.